Pengaruh Kualitas Akrual dan Tata Kelola Terhadap Stock Return - Soni Okabrian; Afifa Nurhanifah; Kamaluddin Rahmat; Venni Avionita (Magister Ilmu Akuntansi Universitas Jambi, 2023)
This study aims to determine the effect of accrual quality through discretionary accruals and governance through institutional ownership, independent commissioners, audit committees and directors on Stock Returns. The study used data from 39 companies included in the Kompas 100 index from 2019 to 2021. The results showed that there was a significant effect on accruals and independent commissioners' discretionary variables on Stock Returns, while for institutional ownership, audit committee and advisory variables had no effect on Stock Returns. . Discretionary accruals have a negative effect on Stock Returns, while independent commissioners have a positive effect on Stock Returns. Taken together discretionary accruals, institutional ownership, independent commissioners, audit committees and directors influence Stock Returns by 14.5%.